(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
The objective of this study was to compare simulated andactual potassium uptake by two crops, using soil and plant parametersobtained from a field experiment conducted in 2003, in Bavaria, southernGermany. Sugar beet (Beta vulgaris L. cv. Kawetina) and wheat (Triticumaestivum L.cv. Star) were grown on a sandy clay loam in the field. The Ktransport in soil and uptake by the plants were simulated by a mechanisticmodel which encompasses uptake by root hairs as well. A sensitivityanalysis was carried out in an attempt to understand the significance ofsingle soil and plant parameters for nutrient uptake. The simulation modelcalculated only 34 % of the measured sugar beet uptake throughout thegrowing period. The lowest calculated K influx (only 9 % of measuredvalue) corresponded to the period June 24th–July 8th of highest actualuptake. Sensitivity analysis showed that, under low K concentrations, Kconcentration in the soil solution was the most important factorcontrolling K uptake, especially for sugar beet. This indicates that rootsmay have increased the K concentration in soil solution by chemicalmobilization. Research is needed to understand the mechanism by whichthis is achieved.